Fahr’s disease: A rare neuropsychiatric disorder - Zeshan Shabbir Sipra; Islah Ud Din; Muhammad Arqam Awais; Taimoor Ali Tariq (Journal of the Pakistan Medical Association, 2022)
Fahr's disease is a rare clinical neurodegenerative entity, occurring mainly in 4th or 5th decade, showing gradually progressive bilateral symmetric calcifications in basal ganglia, subcortical white matter, thalami or cerebellum, which can lead to movement disorder and/or neuropsychiatric manifestations. We present two cases in the same family; a 68-year-old brother had involuntary jerky movements of hand and dysarthria for 10 years while the 44-year-old sister had right lower limb spasticity and decreased vision for 2 years. The serial MRI scans showed slow progression in the bilateral subcortical white matter and cerebellar dentate nuclei calcifications along with surrounding reactive gliosis. Keywords: Symmetrical basal ganglia calcifications, Neuropsychiatric disorder, Familial.